Democracies challenges to societal health - Wejnert, Barbara (Research in political sociology, 2011)
Volume 19 in the Research in Political Sociology series is devoted to health problems, challenges and accomplishments in democratic societies. It includes papers addressing health systems, health policies, obstacles to societal healthy behaviors, and/or health conditions that are experienced in democratic societies in the world. The democratic society is understood in a broadly defined term. It includes developed Western democracies, as well as less developed or underdeveloped countries that have democratic system. According to such definition, the category 'democracies' includes democratic countries that have well established democratic system and respect broad network of people rights, as well as democracies that are formally consider democratic states but de facto respect only a few rights or their governments are guided by limited democratic principles. Therefore, the collection of the 19th volume of Research in Political Sociology includes papers addressing these issues in a broad spectrum of countries from India, Sri Lanka and Tanzania, to Sweden, Canada and the United States.